Maximum Power Point Tracking System for Enhanced Photovoltaic Efficiency Using FPGA - MOHAMAD RAMLI, ABDUL SABIQ; Abdul Hamid, Intan Sue Liana (Evolution in Electrical and Electronic Engineering, 2025)
This project presents the design, simulation, and evaluation of an FPGA-based Maximum Power Point Tracking (MPPT) controller using the Perturb and Observe (P&O) algorithm, implemented in Very High-Speed Integrated Circuit Hardware Description Language (VHDL). The primary objective is to develop an optimum controller to maximize power extraction from a simulated photovoltaic (PV) panel, validated through RTL-level simulation without hardware deployment. The system incorporates a sequencer module that emulates a realistic PV panel I-V curve, with input voltage ranging from 10V to 59V and current from 5A to 0A, mirroring real-world behavior. The controller, designed with an 8-bit resolution and a constrained 10%–90% duty cycle, is synthesized using Altera Quartus II and tested with ModelSim, achieving a Maximum Power Point (MPP) at approximately 20V–26V with a peak power of 104W. Analysis of Power vs. Voltage, Current vs. Voltage, and Efficiency vs. Voltage graphs confirms effective MPP tracking and high efficiency (88%–100%) near the MPP, though post-MPP efficiency anomalies such as  410% are identified as simulation artifacts. In conclusion, the project successfully meets its goals of designing and validating the MPPT controller within the VHDL environment, providing a robust simulation framework. Recommendations for future work include refining the P&O algorithm with adaptive step sizes, enhancing the dcdc_converter model, and planning for hardware-in-the-loop testing to address limitations and transition toward real-world deployment.